Partisipasi Mahasiswa dan Masyarakat dalam Edukasi Kebersihan untuk Menjaga Kualitas Ekosistem Sungai di Surabaya - Agung Satryo Wibowo; Ahmad Nur Raditya Mauludin; Didit Darmawan; Samsul Arifin; Arif Rachman Putra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The river clean-up action around Surabaya is a conservation initiative that emphasizes river environmental cleanliness and responsible waste management. This activity involves various parties, including students, volunteers, local residents, youth, and local government, with the main goal of increasing collective public awareness of the importance of maintaining rivers as vital natural resources. This initiative also aims to minimize negative impacts on aquatic ecosystems and improve the quality of water available to local communities. Through the river clean-up action, the community receives education on good waste management methods and sustainable environmental hygiene practices. The method used is the Participatory Action Research (PAR) method. The results of this activity show that the active involvement of students and the community has a positive impact on the sustainable condition of river cleanliness, including garbage around the roads and river flows that have become cleaner with the reduction of organic and inorganic waste collected around the river flow. This structured and sustainable educational program has been proven to improve students' and community's knowledge and behavior in maintaining river cleanliness. Based on these findings, synergy is needed between the government, educational institutions, and the community to support participatory and sustainable river ecosystem conservation in Surabaya.